Zrozumieć złoty wiek - Nowicka, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
The body of the discussion is devoted to two books, critical editions of Polish translations of the works of Spanish Baroque period, that are related to theatre. The first title in question is the annotated bi-lingual edition of El principe contante by Calderon de la Barca, the drama piece known in Poland as Książe niezłomny [The Constant Prince] and brilliantly translated by Juliusz Słowacki. The other book is the annotated translation of Arte nuevo de hacer comedias en este tiempo [New art of writing plays] by Lope de Vega. Both publications not only evaluate the complex and fascinating picture of Spanish theatrical culture of the Golden Age to the Polish reader, but also substantially widen our understanding of the dependence between the type of the stage and the vision of the world constructed by a playwright and the theatre. They may also provide substantial support, and important inspiration, to theoreticians of theatre and drama, comparatists, historians of ideas, historians of mentality, etc.